Enhancing Interest in Reading Through Letter Puzzle Media in Early Childhood - Irwansyah Irwansyah; Riska Nadya Meilani; Khairuddin Lubis; Armanila Armanila (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2023)
The ability to read is essential for early childhood; seeing the current demands of elementary schools, students who will enter the elementary school level must have the ability to read, so this is urgent for early childhood educators to pay attention to oriented media to current needs. Therefore, this research seeks to enhance interest in reading through the media of letter puzzles in early childhood. Moreover, it aims to discover the inhibiting and supporting factors in increasing interest in reading in early childhood. Through a qualitative descriptive approach, data collection techniques used observation, interviews and documentation are complemented by data analysis techniques, namely data reduction, data presentation and conclusion. The results showed an increase in early childhood reading interest by using letter puzzle media in children's learning activities; this was indicated by the average child achieving learning mastery, meaning developing according to expectations. All of this cannot be separated from the supporting and inhibiting factors in terms of time, children's mood, and media design employed in the teacher's teaching and learning process. Thus, letter puzzle media is an alternative media teacher can use to enhance interest in reading in early childhood. It also helps teachers minimise time and creates a fun learning process for children.